HUBUNGAN GAYA KEPEMIMPINAN DAN PENDIDIKAN-PELATIHAN TERHADAP KINERJA DOSEN (STUDY KASUS DI LP3I KAMPUS CARINGIN – TOMANG JAKARTA PUSAT) - Dedi Royadi (JURNAL LENTERA BISNIS, 2012)
The head of branch is a formal leader in his campus. They are in charge of managing lectures to develop their performance and achievement. By increasing their skills and potential, the lectures will be good partners in education fields and giving positive attitude to their profession in order to make students graduating more qualified. Polytechnic LP3I Caringin - Tomang, as one of new LP3I branches needs an integrated education vision between the lectures and the head of branch to increase their performance and achievement by training continually.The problem statement is “Are there any significant correlation between the leaderships style and education training to their achievement?”. This study is part of a larger study that used survey and the methodology is analysis descriptive which is a research method by taking sampling in certain population by using questioner.It is stated that there is significant positive effect from leadership style and education training to lecture achievement by using 81,8% variant in determination confession. The leadership style got 0,395 regressions while training got 0.881 regressions.The result of this research is suggested to develop their teaching method in other to be able to maximize the learning result by increasing training, book resources and internet. It will make additional value to the professional lecture.Keywords: performance, achievement, leaderships style, and education training.